SIMTOMATOLOGI PADA PASIEN STROKE BERDASARKAN DISTRIBUSI JENIS PATOLOGI - , ALFA MONICA ARNORISA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Time stroke handling is very influential to prognosis stroke that of course needs speed in determining diagnosis. Thus I'd like to do research to see signs and symptoms are the most emerged in each type of stroke. Purpose: The purpose of this research is to know distribution and percentage signs and symptoms stroke patients in Stroke Unit RSUP HAM), one baby was Dr. Sardjito Yogyakarta based on distribution of pathology. Method: Research carried out in Installing Medical Records Stroke Unit General Hospital Center Dr. Sardjito. In this research that will be used as instrument is medical records new patients Stroke Unit RSUP HAM), one baby was Dr. Sardjito. Signs and symptoms would have been recapitulated from medical records that had been arranged like a checklist. The criteria inclusion on all new patients first noted as patients Stroke Unit RSUP HAM), one baby was Dr. Sardjito Yogyakarta. Data analysis techniques used in this research is a technique quantitative data analysis. Data analysis done with the help software SPSS v. 18 and the result was changed to form percentage, made clear to diagram pie symptoms and signs to see based on distribution of pathology. Results: Types of pathology stroke that most often found on ischemic stroke patients (64 percent). While for stroke bleeding most is bleeding intracerebral (82%). Clinical symptoms that dominant appeared in patients with ischemic stroke arecranial nerve paresis (74%) and impaired motor (65%). Clinical symptoms that dominant appeared in stroke patients bleeding intracerebral is cranial nerve paresis (64%) and impaired motor (58%). There is no clinical symptoms dominant that appeared in the elderly bleeding subarachnoid. Conclusions: symptoms dominant in both ischemic stroke and stroke bleeding intracerebral is cranial nerve paresis, while in stroke bleeding subarachnoid there is no symptoms that dominant.